New Insights Into the Interplay Among Autophagy, the NLRP3 Inflammasome and Inflammation in Adipose Tissue - Zhu, Liyuan; Liu, Ling (Frontiers in Endocrinology, 2022)
Obesity is a feature of metabolic syndrome with chronic inflammation in obese subjects, characterized by adipose tissue (AT) expansion, proinflammatory factor overexpression, and macrophage infiltration. Autophagy modulates inflammation in the enlargement of AT as an essential step for maintaining the balance in energy metabolism and waste elimination. Signaling originating from dysfunctional AT, such as AT containing hypertrophic adipocytes and surrounding macrophages, activates NOD-like receptor family 3 (NLRP3) inflammasome. There are interactions about altered autophagy and NLRP3 inflammasome activation during the progress in obesity. We summarize the current studies and potential mechanisms associated with autophagy and NLRP3 inflammasome in AT inflammation and aim to provide further evidence for research on obesity and obesity-related complications.